CURCUMIN AS ACID/BASE INDICATOR: A STATISTICAL ANALYSIS - Silva, Annielly Fernanda de Sousa; Leme, Paulo Cesar; Gonçalves, Joyce Laura da Silva (Revista FACISA ON-LINE, 2022)
Since the world became aware of environmental issues, natural pH indicators have been widely study to replace those synthetics to identify the end point of acid-base titrations. However, most studies only present qualitative evidence for the use of these indicators. In this paper, the Curcumin (CUR) application viability in volumetric titrations as pH natural indicator was performed not only qualitative but also quantitative analysis in comparison to phenolphthalein. The methodology employed was visual, spectroscopic and statistical hypothesis tests (p< 0.05). The qualitative results showed that the CUR changed color as a function of pH and its application was clear, fast and satisfactory as an acid-base indicator. Such color changes were assigned to the CUR keto-enol tautomerism and characterized by UV-Vis. By quantitative analysis, it was observed that there were no significant differences between the both confidence interval of the means for the calculated hydrochloric acid (HCl) and acetylsalicylic acid (ASA) concentration titrated by CUR and phenolphthalein as an indicator. The same observations was done by the paired t-test with comparable standard deviation. It suggests that CUR can easily replace phenolphthalein on the acid-base volumetric in a low-cost, affordable and eco-friendly way, especially on the chemical education.